Maturzyści o wartościach – deklaracje, oczekiwania, wnioski - Kopeć, Urszula (Dydaktyka Polonistyczna, 2019)
The article discusses the results of studies on values declared by high school graduates. The survey was conducted in September 2017 in two high schools in Rzeszów. 130 respondents were asked to point out 3 of the most treasured positive values and 3 of the most undesirable anti-values. The high school graduates were also asked what they expected from their Polish teachers who discover the world of values with them. The analysis of students’ answers indicates that high school graduates appreciate the most the following values: love, family, friendship. By contrast, they consider hatred, falsehood, disease and egotism to be the most unwanted anti-values. In the respondents’ view it is worth discussing thoroughly and delving into the meaning of notions such as: erotic love, friendship, freedom or hatred.